1997
DOI: 10.2307/2446617
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, genetic diversity, and clone formation in Quercus chrysolepis (Fagaceae)

Abstract: Stands of canyon live oak (Quercus chrysolepis, Fagaceae) are maintained for fuelwood, fire management, recreation, and as habitat for wildlife. Information about the link between the oak's reproductive ecology and its extent of genetic diversity is important in developing land management policies that will maintain the long-term viability of populations. Basal sprouting is the primary means of reproduction following fire or cutting, and stands frequently include groups of visibly connected trees in a clustere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 69 publications
(64 reference statements)
7
66
3
Order By: Relevance
“…Previously reported ranges of individuals or clumps of ramets include 2-4 m in Fagus japonica (Kitamura et al, 1992), 4 m in Quercus chrysolepis (Montalvo et al, 1997), 8 m in Fagus grandifolia (Jones and Raynal, 1987), and areas of 50 m 2 in Thujopsis dolabrata (Hashimoto et al, 1999) and up to 43 ha in Populus tremuloides (Kemperman and Barnes, 1976). Thus, the A. trabeculosa range found in this study was similar to those of F. japonica and Q. chrysolepis.…”
Section: Naoko Et Alsupporting
confidence: 84%
“…Previously reported ranges of individuals or clumps of ramets include 2-4 m in Fagus japonica (Kitamura et al, 1992), 4 m in Quercus chrysolepis (Montalvo et al, 1997), 8 m in Fagus grandifolia (Jones and Raynal, 1987), and areas of 50 m 2 in Thujopsis dolabrata (Hashimoto et al, 1999) and up to 43 ha in Populus tremuloides (Kemperman and Barnes, 1976). Thus, the A. trabeculosa range found in this study was similar to those of F. japonica and Q. chrysolepis.…”
Section: Naoko Et Alsupporting
confidence: 84%
“…marina clones show spatial fragmentation (clone structure (b) Figure 2 and Table 1). Spatially separated groups of trees with identical genotype also indicated such a structure to be present in Quercus chrysolepsis (Montalvo et al, 1997). In the latter study, it was probably responsible for values of coancestry too high to be explained solely by limited dispersal.…”
Section: Discussionmentioning
confidence: 56%
“…Our values from the analysis including all samples range from 0.028 to 0.161 for the 2 m interval (Table 1). For the same distance, autocorrelation values from Louisiana iris hybrid populations showed a range of E0-0.2 (Burke et al, 2000) and for populations of canyon life oak E0.38-0.42 and 0.25 excluding multiple samples per genet (Montalvo et al, 1997). For the marine environment, Coyer has reported significant coancestry values of 0.060-0.092 for Z. noltii (Jim Coyer, unpublished data) at the 2 m scale and JL Olsen reported significant coancestry of 0.25 for Ascophyllum sp on a scale of 40 cm-1 m (Jeanine L Olsen, unpublished data).…”
Section: A Hämmerli and Tbh Reuschmentioning
confidence: 89%
See 1 more Smart Citation
“…Outcrossed, insect-pollinated plants are predicted to have moderate to high gene flow (Loveless and Hamrick 1984; but see Hogbin et al 1998). Montalvo et al (1997) found that canyon live oak similarly lacked genetic subdivision and showed high levels of gene flow between populations more distantly separated than ours. In our system, seeds from Bayshore, the Dunes, and Mussel Point are likely to be genetically similar because of very low F ST -values.…”
Section: Genetic Structurementioning
confidence: 53%